Particle Movement in Paper Porous Media: Influence Factors and Model - Hsu, Hsuan Huan (My University, 2010)
In recent years, paper-based analytical devices have been widely applied in many areas such as chemical analysis, disease diagnosis, and contaminant sensing. From the most common utility in pH paper to novel electrochemical sensing devices for monitoring heavy metals or glucose (2), paper-based analytical devices have shown great potential to become alternative analytical technologies. In paper based analytical device, commonly, the samples are transport by the capillary force from enter site toward the testing area. However, there is still not enough information of sample transportation in paper. This research focused on understanding the particle movement during elution in paper in order to provide some useful information for design and manufacture of paper analytical devices.
There are many factors that influence the particle movement in paper, such as particle properties (i.e. surface potentials), paper properties (i.e. salt content on paper) and ambient factors (i.e. humidity). The effects of those factors on particle movement in paper were studied by the elution experiments. The elution experiments were conducted by vertically dipping the bottom 1 cm of paper strips (Whatman No.1) into polystyrene latex solutions. The latex solutions were eluted up by the capillary force of paper, which was spontaneously occured due to the porous structure of paper. Then, by varying the testing factors, respectively, the effects caused by those factors can be investigated.
Since paper is composed of cellulose with many carboxyl groups, it is negatively charged. Therefore, the surface potential of particles was considered as an important factor that influences particle movement and deposition. More deposition was observed when particles with more positive charge were eluted in paper and vice versa. In addition, the influence of the flow velocity on particle movement during elution was also studied. The flow velocity was varied by changing the shape of paper strips. No obvious influence of the flow velocity on anionic particle deposition was observed, while the raise of the flow velocity increased cationic particle deposition. Moreover, the paticle (cationic and anionic) deposition was increased when latexes flowed through paper strips with salt content. The salt was dissolved once it contacted by the elution flow, which resulted in the increase of ionic strength in the elution flow. As a result, increased particle deposition were observed due to the reduced electrical double layer repulsive forces (particle-particle and anionic particle-paper surface) caused by increased ionic strength.
Nevertheless, in all the experiments described before, it was noted that there was always a band shape of concentrated particles at the elution end (where elution flow stopped flowing forward). This phenomenon was caused by the mass flow (MFE), which occurred in order to refill the water loss due to evaporation. After the capillary flow reached the elution end, the suspended particles were carried continuously up to the elution end by MFE and concentrated gradually. To describe the movement of this evaporation-driven flow, the model suggested by Fries (29) (Eq. 4.2.11) was applied. The results predicted from this model fitted the experimental data well. The influences of evaporation on elution flow movement were further investigated based on this model. The effects of paper properties on the maximum elution distance were also examined based on the model of Fries (29) (Eq. 4.2.11). The results showed the influences of paper properties were in the order as: pore radius (capillary radius (Rs)) > permeability (K) ≒ thickness (δ) > contact angle (θs)> porosity (ϕ) (no effect).
Keywords: Chemical Engineering; Chemical Engineering